Effect of Partial Shading and Performance Analysis on Various Array Configurations of Photovoltaic System - Ajmal A.M.; Babu Thanikanti S.; Ramachandaramurthy V.K.; Ekanayake J.; Tariq M. (Institute of Electrical and Electronics Engineers Inc., 2023)
MATLAB; Photovoltaic cells; Array configurations; Comparative studies; Non-uniform irradiation; Partial shading; Performance analysis; Photovoltaic arrays; Photovoltaic systems; Series-parallel; Photovoltaic effects